Study of citizen satisfaction and loyalty in the urban area of Guayaquil: Perspective of the quality of public services applying structural equations. - María Salomé Ochoa Rico; Arnaldo Vergara-Romero; José Fernando Romero Subia; Juan Antonio Jimber Del Río (PLoS ONE, 2022)
This study investigates the satisfaction and adequacy of citizens through the expected quality and perceived quality in the areas of planning and territorial viability, experience in the provision of municipal services and citizen experience in environmental issues, in order to provide tools for territorial decision making for the citizens' well-being. In our research PLS software is used for the analysis of hypotheses. A questionnaire was delivered to a sample of 521 citizens, representing the spectrum of the population, and the statistical study of the responses yielded results on citizen satisfaction and loyalty. Our research includes the study of moderating effects on the causal ratio of perceived value and satisfaction in territorial planning and viability, the perceived quality in the provision of municipal services and the perceived quality in the citizen experience in the environmental management of the territory on the value relationship perceived by the citizen and general satisfaction. A second objective of the study is to see if there are significant differences in the hypotheses raised by gender by performing a multigroup analysis. This difference has been appreciated in two of the hypotheses. The study shows that the policies exercised by the territorial managers of the different areas have a significant influence on the value perceived by citizens, satisfaction and loyalty, which shape their general well-being. Areas for improvement in territorial policies and municipal services such as citizen security, air quality, public lighting and sports services have been identified. Knowing these shortcomings allows politicians to focus their efforts on improving the quality of life in cities.